The contribution of alliaceous and cruciferous vegetables to dietary sulphur intake. (1st November 2017) - Doleman, Joanne F.; Grisar, Katrijn; Van Liedekerke, Lena; Saha, Shikha; Roe, Mark; Tapp, Henri S.; Mithen, Richard F.
Highlights: Sulphur intake estimation based upon methionine and cysteine overlooks contributions from other sources. Intake estimations for sulphur from diet diary and duplicate diet agree well. There is no requirement for mass re-analysis of the sulphur content of foods. Caution is advised for diet diary analysis estimations of zinc and sodium. Abstract: Despite its importance in many areas of human metabolism, there are no recommended daily intake guide lines for sulphur. It is generally assumed that most dietary sulphur originates from intake of methionine and cysteine. We estimated sulphur intake from food diaries, and validated the results with the use of a duplicate diet analyses. Sulphur intake estimations were highly correlated with that obtain through an elemental analysis of duplicate diets, with a mean ± sd daily intakes of 956 ± 327.9 mg estimated from diet diary analyses and 935 ± 329.9 mg estimated by a duplicate diet analyses. Sulphur intake from alliaceous and cruciferous vegetables contributed up to 42% of total sulphur intake. Daily intake estimation comparisons through diet diary analyses and duplicate diet for other elements showed good agreement, except for sodium and zinc, in which analyses of 24 h diet dairies overestimated intake by 35% and 52%, respectively.